Surgical Sealing of Laterally Localized Accessory Root Canal with Resin Containing S-PRG Filler in Combination with Non-Surgical Endodontic Treatment: A Case Report - Shizu Hirata-Tsuchiya; Shigeki Suzuki; Takashi Nakamoto; Naoya Kakimoto; Satoru Yamada; Hideki Shiba (MDPI AG, 2020)
The spread of root canal infection to surrounding periodontal tissue through accessory root canals reduces the success rate of endodontic treatment. In this case, cone-beam computed tomography revealed a lesion (4 mm from the apex) resulting from an accessory root canal of the maxillary left central incisor. First, non-surgical endodontic treatment was conducted but the sinus tract remained. Surgical preparation of the root cavity was then conducted to remove potentially infected dentin surrounding the accessory root canal. The cavity was filled and the foramen was sealed with resin containing bioactive surface pre-reacted glass (S-PRG) filler. The photopolymerized resin was then contoured and polished. In combination with subsequent supportive non-surgical endodontic treatment, a good clinical outcome with the disappearance of the sinus tract and clinical symptoms such as discomfort and pressure pain and the regeneration of the alveolar bone hanging over the cavity was obtained. In this case, the good clinical outcome may have been due to the dentin-adhesive property and durability of the pre-adhesive system and composite resin. The better biocompatibility of S-PRG fillers presumably facilitated periodontal tissue healing.